Airfreight Forwarder’s Short-term Space Allocation Problem with the Cost of Transit Time and Its Long-term Block Space Agreements - Thamtiang, Nithima; Pongsathornwiwat, Akkaranan; Amaruchkul, Kannapha (Thai Industrial Engineering Network Journal, 2022)
This article considers the carrier selection problem and the short-term freight allocation problem for an air freight forwarder, when the total demand exceeds the total space from the block space agreement (BSA). We propose a mixed-integer linear programming model for these two problems, whose decisions greatly affect the freight forwarder’s cost. Our model considers both the freight charge and the cost of transit time so that a direct flight is preferred to a non-direct flight. In the case study, we apply our model to the actual export demand during April 2020-July 2021; the top five export traffic lanes are Narita, Hong Kong, Shanghai, Manila and Jakarta, respectively. When we compare to the actual operations during the average month in each lane, we find that our model reduces the cost by 3.05% or approximately 15 million THBs. Furthermore, we perform sensitivity analysis with respect to the capacity per pallet and the cost of transit. We find that as the capacity per pallet increases, the cost decreases. When the transit cost is sufficiently high, the direct flights are always selected; therefore, the freight charge remains the same.